Preliminary Study on the Use of Reclaimed Asphalt in Public Works Authority Road Projects in the State of Qatar - Santagata, Ezio; Yeganeh, Sadegh; Sebaaly, Haissam; Elhussein, Osman; Al Marri, Ali Mohammed (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2023)
This paper describes the outcomes of a preliminary study focused on the evaluation of four full-scale pavement sections in which reclaimed asphalt (RAP) was used in partial substitution of virgin aggregates during the production of asphalt mixes. Considered mixes were produced with different RAP percentages and were thereafter laid on site for the formation of asphalt base course layers of pavements in local roads of the State of Qatar. For comparative purposes, two trials included asphalt mixes containing no RAP, and in one case use was made of a rejuvenating agent. Activities carried out for the monitoring of field trials included analysis of component materials, critical observation of production and laying operations, assessment of the most relevant characteristics of produced asphalt mixes, and evaluation of the degree of compaction achieved during construction. Experimental results were of crucial importance for the introduction of RAP-related paving technologies in the State of Qatar, providing a meaningful background to the preparation of the Ashghal Recycling Manual issued by Ashghal and of the draft updated version of Qatar Construction Specifications.